2002
DOI: 10.1136/ard.61.2.174
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 13 in synovial fluid and serum of patients with psoriatic arthritis

Abstract: Objectives: To compare the pattern of interleukin (IL) 13 production in synovial fluid (SF) and serum of patients with psoriatic arthritis (PsA) with that in patients with rheumatoid arthritis (RA) and osteoarthritis (OA), investigating its relation to the proinflammatory cytokine IL12. Methods: SF and serum IL13 levels were determined in 35 patients with PsA, 36 with RA, and 15 with OA. The main clinical and laboratory variables, including number of painful and/or swollen joints, Ritchie index, morning stiffn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 12 publications
1
25
0
1
Order By: Relevance
“…Initial studies showed that IL-13 mRNA levels do not differ significantly between lesional and non-lesional skin samples from psoriasis patients [29], [30]. Subsequent studies confirmed this result, but also showed that mRNA encoding the α1 chain of the IL-13 receptor is over-expressed in lesional skin relative to normal skin from healthy controls [31], and further demonstrated that IL-13 is elevated in synovial fluid of patients with psoriatic arthritis [32]. Moreover, a large genome-wide association study, including 3523 cutaneous-only psoriasis cases, 1755 psoriatic arthritis cases, and 5942 unaffected controls, reported that both cutaneous-only psoriasis and psoriatic arthritis were associated with an exonic IL-13 locus on chromosome 5q31 (rs20541) [33]; however, recent analyses suggest that this association is stronger with respect to psoriatic arthritis, or even specific to psoriatic arthritis with no significant association to cutaneous-only psoriasis [34], [35].…”
Section: Discussionmentioning
confidence: 94%
“…Initial studies showed that IL-13 mRNA levels do not differ significantly between lesional and non-lesional skin samples from psoriasis patients [29], [30]. Subsequent studies confirmed this result, but also showed that mRNA encoding the α1 chain of the IL-13 receptor is over-expressed in lesional skin relative to normal skin from healthy controls [31], and further demonstrated that IL-13 is elevated in synovial fluid of patients with psoriatic arthritis [32]. Moreover, a large genome-wide association study, including 3523 cutaneous-only psoriasis cases, 1755 psoriatic arthritis cases, and 5942 unaffected controls, reported that both cutaneous-only psoriasis and psoriatic arthritis were associated with an exonic IL-13 locus on chromosome 5q31 (rs20541) [33]; however, recent analyses suggest that this association is stronger with respect to psoriatic arthritis, or even specific to psoriatic arthritis with no significant association to cutaneous-only psoriasis [34], [35].…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, IL13 polymorphisms were also associated with high serum levels of IL-1325 and a recombinant IL-13 protein of one of these variants (glutamine substitution for arginine at position 110 on the mature protein, Arg110Gln) has demonstrated greater biological activity 26. Although the role of IL-13 in psoriatic disease is unclear, several studies have found increased levels of the cytokine in the serum and synovial fluid from PsA patients 14 15 27. It was suggested that IL-13 may be important in the regulation of active joint inflammation, as IL-13 inhibits Th1 activity and was reported to have an antiarthritic effect in an animal model of collagen-induced arthritis 15 28…”
Section: Discussionmentioning
confidence: 99%
“…High levels of IL-13 were found in synovial fluid from actively inflamed joints of patients with PsA but not in psoriatic skin 14. The role of IL-13 in the pathogenesis of PsA is unclear, as inflammatory arthritis is mainly a process that is mediated by Th1 pro-inflammatory cytokines, including tumour necrosis factor α and IL-1.…”
mentioning
confidence: 99%
“…26 The participation of IL-13 in psoriasis has been reported previously. For example, IL-13 has been detectedin the synovial fluid and serum of patients with psoriatic arthritis, 42 and the mRNA of IL-13Ra1 and IL-4Ra (both IL-13 receptors) is overexpressed in the skin of psoriatic patients. 23,43 Also interesting were the findings showing that, in lung-targeted VEGFtransgenic mice, IL-13 is overproduced.…”
Section: Inmentioning
confidence: 99%